Longitudinal analysis of cognitive constructs fostered by STEM activities for middle school students - Christensen, R.; Knezek, G.; Tyler-Wood, T.; Gibson, David (Hong Kong Bao Long Accounting And Secretarial Limited, 2014)
The purpose of this study was to determine whether the changes found to occur pre- to post intervention in students' cognitive structures continued to persist two years later. Major findings were: 1) higher-order STEM-related constructs established during the treatment year tended to persist two years later, even as component dispositions varied, and 2) gender differences in level of persistence emerged in only one of the four higher-order constructs identified. For the participants taken as a whole, perceptions of science and STEM as a career became more aligned with interest in being a scientist, from pretest to posttest time during the treatment year and continued to be aligned two years later. Perception of engineering moved from alignment with science and STEM as a career at time 1, to alignment with perception of technology and creative tendencies after the treatment year, at time 2, and remained aligned with technology two years later, at time 3. Perception of mathematics was separated from the other constructs during the pre-post treatment year and remained largely separated two years later. One subscale of the career interest survey focusing on working with others to make the world a better place through science, separated from other career interest subscales and became its own higher-order construct at time 2, and still remained on its own at time 3. Data mining techniques as well as higher-order factor analysis were used to identify changes in relationships among these and other constructs over time.